Larval fish distribution and retention in the Canary Current system during the weak upwelling season. (22nd February 2014) - Moyano, M.; Rodríguez, J.M.; Benítez‐Barrios, V.M.; Hernández‐León, S.
Abstract The spatial distribution of fish larvae was studied in the Canaries‐African Coastal Transition Zone, outside the strong upwelling season. An onshore–offshore transition in the larval fish community structure was observed, from a coastal assemblage dominated by small pelagics (sardine, anchovy, mackerel), bounded by the upwelling front, to an offshore assemblage dominated by mesopelagic species (mainly Myctophidae, Phosichthydae, Gonostomatidae). Distribution of the neritic larvae was deeply influenced by the intense mesoscale activity found in the area, both horizontally (larvae were advected offshore but were always retained within the upwelling area) and vertically (larvae were deepened in the vicinity of two anticyclonic eddies). A combined effect of the upwelling front and a cyclonic–anticyclonic eddy dipole is likely the successful retention mechanism for these larvae. These results support the current belief that retention may be higher than previously thought in upwelling areas. Oceanic larvae were also collected in higher abundances near the front and an anticyclonic eddy. Neritic and oceanic larvae frequently showed a differentiated position in the water column, although they sometimes coexisted. Finally, larval connectivity between Islands within the Canary archipelago is suggested. The present study thus contributes to the understanding of the complex dispersal and retention processes in the Canaries‐African Coastal Transition Zone. However, results also highlight the poor knowledge of this region compared with the other three main Eastern Boundary Upwelling Systems in terms of ichthyoplankton dynamics. The importance of routine monitoring programs of commercial and non‐commercial species in the area is emphasized.